A resurgent presidency? Portuguese semi-presidentialism and the 2016 elections - Fernandes, Jorge M. (2018)
This article analyses the Portuguese presidential elections of January 2016, setting these within the backdrop of recent semi-presidential practice in Portugal. The election took place in the context of an apparent hollowing of the presidency, a pattern that potentially reflects the bailout that marked most of the second term of the outgoing president, Cavaco Silva. This pattern also helps explain the second-order nature of this presidential election. Despite potentially being an ‘open’ election – in that the incumbent had reached term limits – the election was characterised by low citizen mobilisation, low partisan involvement and low competitiveness. The initial two months of the newly elected president, Marcelo Rebelo de Sousa, suggests he is seeking to invert this hollowing pattern by mobilising popular support behind the presidency.